2005
DOI: 10.1177/0269881105056657
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram slowing, sleepiness and treatment response in patients with schizophrenia during olanzapine treatment

Abstract: Electroencephalogram (EEG) slowing is associated with clozapine side effects, e.g., sedation, and may predict treatment response during clozapine treatment. As olanzapine and clozapine share many pharmacological properties, we investigated whether EEG slowing during olanzapine treatment was related to therapy outcome and sleepiness in patients with schizophrenia. Participants were age- and gender-matched schizophrenic patients treated with olanzapine (n 54), receiving no pharmacological treatment (n 54), or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
(23 reference statements)
2
10
1
1
Order By: Relevance
“…However, VU0467154 did not alter the power spectra when administered during the dark period while rodents are most alert, consistent with a lack of potential sedating or hyper-arousing effects of the M 4 PAM mechanism. In contrast, clozapine increased low, and decreased high power, consistent with the sedative effects of APDs in medicated patients with schizophrenia (Boutros et al, 2008; 2014; Goder et al, 2006; Keshavan et al, 1995a; Wichniak et al, 2006). Clozapine and xanomeline administration produced similar effects, regardless of dosing during the light or dark period.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…However, VU0467154 did not alter the power spectra when administered during the dark period while rodents are most alert, consistent with a lack of potential sedating or hyper-arousing effects of the M 4 PAM mechanism. In contrast, clozapine increased low, and decreased high power, consistent with the sedative effects of APDs in medicated patients with schizophrenia (Boutros et al, 2008; 2014; Goder et al, 2006; Keshavan et al, 1995a; Wichniak et al, 2006). Clozapine and xanomeline administration produced similar effects, regardless of dosing during the light or dark period.…”
Section: Discussionsupporting
confidence: 59%
“…However, the effects of clozapine and other APDs on sleep do not substantially improve cognition (Barch and Ceaser, 2012; Nuechterlein et al, 2004), perhaps due to residual sedative effects during wake. Daytime drowsiness or decreased arousal is common following APD administration in healthy humans, schizophrenia patients, and in healthy rats (Ahnaou et al, 2003; Czobor and Volavka, 1993; Dimpfel, 2007; Hughes et al, 1999; Roubicek and Major, 1977; Wichniak et al, 2006; Yoshimura et al, 2007). In the present studies, VU0467154 altered sleep in a manner similar to clozapine, suggesting potential APD-like activity on sleep architecture, but lacked the sedative profile of clozapine during waking periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wichniak et al [20] reported that the risk of epileptic seizures under olanzapine treatment can be regarded as low as long as olanzapine is administered as a monotherapy. In addition to this, an excess increase in the dosage of olanzapine should be regarded with caution.…”
Section: Discussionmentioning
confidence: 99%
“…(5,9,10) Quanto às anormalidades do EEG, em nossos casos não houve lentificação da atividade elétrica cerebral de base que é o achado mais freqüente associado à olanzapina. (4,9,10,11) Em relação à AE ao EEG, com o uso de olanzapina, há poucos relatos na literatura e, estes por vezes, são contraditórios.…”
Section: Discussionunclassified